Body weight gain and development of reproductive tract in crossbred Murrah × Mediterranean water buffalo heifers - Oswaldo J. González; Amílcar Acuña; Solaine Bradley; Ysis Cañizalez; Jorge Espinoza; Cindy Paniagua; María Virginia Suárez; Mónica Fuentes (Revista Científica)
The objective of this study was to evaluate the effects of supplementation that include a Saccharomyces cerevisiae commercial yeast culture (Nutrit Yeast®, Barquisimeto, Venezuela) on average daily gain (ADG) and development of the reproductive tract in crossbred Murrah x Mediterranean water buffalo heifers with poor weight gain in the central-western region of Venezuela, Lara state. The buffalo heifers (middle age: 710 days old and middleweight: 237 Kg) were randomly assigned to one of two treatments for 174 days. A treated group (n=35) was fed 1kg of a concentrate animal/day plus 5g of Saccharomyces cerevisiae yeast/animal/day, and a Control group (n=36) did not receive the supplementation. The heifers grazed in the same pastures and received the same fresh-cut grass at the herd and the same mineral supplementation. All animals were weighed and evaluated, and the reproductive tract score (RTS) was assessed by rectal palpation every 45 days. During the test, the animals gained 94.5 ± 25.5 Kg and 59.6 ± 38.5 Kg, treated and non-treated heifers, respectively. At the end of the study, the qualifiers of the reproductive tract, 26.5%, and 3.6%, were observed in a cyclical state by treated and non-treated, respectively. The weights of the animals were analyzed by linear regression, and the qualifier of the reproductive tract by non-parametric statistics. When comparing the results between supplemented and non-supplemented heifers, highly significant differences (p˂0.01) were observed between both groups in ADG since supplementation began and was kept throughout the study. In addition, for the gynecological examination, a median of Wilcoxon comparison test was performed, showing highly significant differences between supplemented and non-supplemented from the beginning of supplementation, observing a lower percentage of heifers in gynecological infantile uterus condition in supplemented ones, even increasing the percentage of heifers in the development and active stage. In conclusion, the supple-mentation, including the yeast culture increase, significantly enhanced the body weight gain and reproductive tract development in water buffalo heifers.